2016
DOI: 10.1007/s00296-016-3505-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the reliability of the Thai version of the Hip disability and Osteoarthritis Outcome Score (HOOS)

Abstract: HOOS was developed as an extension of the Western Ontario and McMaster Universities' Osteoarthritis Index questionnaire for measuring symptoms and functional limitations related to the hip(s) of patients with osteoarthritis. To determine the validity and reliability of the Thai version of the Hip disability and Osteoarthritis Outcome Score (HOOS) vis-à-vis hip osteoarthritis, the original HOOS was translated into a Thai version of HOOS, according to international recommendations. Patients with hip osteoarthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The results of the assessment of the internal consistency were good for all subscales and were comparable to those observed in other language versions of the HOOS [ 4 7 , 9 ] suggesting good homogeneity. Cronbach’s alpha ADL subscale scored the highest value (0.96), according to the French (0.94) [ 4 ], Dutch (THA) (0.95) [ 5 ], Korean (0.96) [ 6 ] and original HOOS (0.96) [ 1 ] validation studies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of the assessment of the internal consistency were good for all subscales and were comparable to those observed in other language versions of the HOOS [ 4 7 , 9 ] suggesting good homogeneity. Cronbach’s alpha ADL subscale scored the highest value (0.96), according to the French (0.94) [ 4 ], Dutch (THA) (0.95) [ 5 ], Korean (0.96) [ 6 ] and original HOOS (0.96) [ 1 ] validation studies.…”
Section: Discussionsupporting
confidence: 80%
“…The convergent validity was tested by using Spearman’s rank correlation coefficient between the results of each HOOS and SF-36 subscales. Spearman’s correlation coefficients (rho) > 0.50, 0.35–0.50, and < 0.35 were considered strong, moderate and weak correlations, respectively [ 6 , 7 , 9 ]. As reported by Scalone et al [ 23 ], to be considered relevant for convergence, the correlation coefficients between equivalent domains are required to be higher than 0.2 and statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…However, this study used a large cohort, followed prospectively, and used a longer period of follow-up than that the majority of studies reported. This study was performed in Thailand in the Thai language, but all the PROs used have been previously validated in Thai [28][29][30][31]. Finally, this was an observational study using usual care rather than an intervention; the comparability of generic vs. SLE-specific HRQoL instruments needs to be confirmed in the setting of an interventional trial with an effective agent.…”
Section: Discussionmentioning
confidence: 99%
“…SLEQOL was developed in Singapore and incorporates questions suitable for oriental cultures [7]. Both SLE-QOL and SF36 surveys have been translated into Thai, validated [28,29], and used in many clinical studies in Thailand [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate the interpretation of responses to interventions and in clinical decision-making, a comparison with appropriate reference values is essential [ 12 ]. However, there is a lack of reference data for many clinical measures from the general population, in particular with regard to the relationship between demographic factors and self-reported hip status [ 12 ].…”
Section: Introductionmentioning
confidence: 99%